Hydrogen Sulfide Regulates Inward-Rectifying K+ Channels in Conjunction with Stomatal Closure - Papanatosiou, Maria (2015)
Hydrogen sulfide (H2S) is the third biological gasotransmitter, and in animals, it affects many physiological processes by modulating ion channels. H2S has been reported to protect plants from oxidative stress in diverse physiological responses. H2S closes stomata, but the underlying mechanism remains elusive. Here, we report the selective inactivation of current carried by inward-rectifying K+ channels of tobacco (Nicotiana tabacum) guard cells and show its close parallel with stomatal closure evoked by submicromolar concentrations of H2S. Experiments to scavenge H2S suggested an effect that is separable from that of abscisic acid, which is associated with water stress. Thus, H2S seems to define a unique and unresolved signaling pathway that selectively targets inward-rectifying K+ channels.